A CLINICAL STUDY OF KNEE JOINT LIGAMENT INJURY WITH KARKADA TAILA - A CASE REPORT - chathiyath, Lakshmy; Deep, V.C.; Acharya, M.V. (International Journal of Ayurveda and Pharma Research, 2017)
Knee the prominent hinge joint which provides a variety of movements, makes a flexible life, is termed as Janu sandhi in Ayurveda. Ligament injuries of Knee has become an upsetting quandary in medical fraternity, moderate to severe, often poses variation of management from simple rest to reconstructive surgeries. These injuries related specially to sports personalities often impede their sustaining options in their field, ultimately hampers their hope of success, by all means. Even though reconstructive surgeries are celebrated a lot for this, their non judicial use even for a grade I injury paves many difficulties for patients of poor economic status. Ayurveda generally not going behind surgical methods, should find an aspirating solution in this regard. So an alternative cost effective modality is the need of time. With many discussions and trials here is a special preparation made in CARIN & MSD, Cheruthuruthy, which involved its internal intake as well as external use with which the major problems associated with Ligament injury are managed efficiently. Special Taila was used for 21 days and obtained enthusiastic result in this regard. Being a young age patient the result obtained was very sudden and complete. Here it was done for cruciate ligament injury. Other injuries like meniscal tears, collateral ligament should also be tried with the same Taila. The medicines organoleptic and biochemical evaluation can also be conducted further. Its use in other joint injuries may also be a considered as a matter for further studies.